Союз лингвистики и промпт-инжиниринга: лингвистические особенности запросов к нейросети - Stetsyk, Marianna (Vilnius University Open Series, 2024)
This article offers a linguistic perspective on the study of the interaction between humans and Artificial Intelligence. The focus of the work is on analyzing human communication with neural networks which generate textual content. With the advent of text-based interfaces for neural networks, where programming skills are no longer required for human-AI communication, and it is sufficient to create text queries (prompts), one of the key skills for prompt engineers (specialists in prompt creation) has become the ability to ‘program’ and obtain AI responses corresponding to the query while using natural language resources. This work is aimed at studying, identifying, and describing the linguistic features of prompts and their parameters that influence the stylistic correctness of the generated responses by the neural networks.
Keywords: промпт; промпт-инжиниринг; нейросеть; стилистика; стилистические маркеры